Inhibition effect and mechanism of mesoporous silica hollow nanospheres on asphalt VOCs. Issue 2 (5th April 2019) - Shu, Benan; Wu, Shaopeng; Li, Chao; Long, Yongshuang; Liu, Quantao
Abstract : In this study, mesoporous silica hollow nanospheres (MSHSs) with continuously distributed pore diameters were simply synthesized through the hydrothermal method. Then, the effect of MSHSs on inhibition of asphalt volatile organic compounds (VOCs) was studied by using pyrolysis–gas chromatography/mass spectrometry (GC-MS). In addition, scanning electron microscopy, transmission electron microscopy, Fourier transform infrared spectroscopy and the Brunauer–Emmett–Teller method were conducted to analyze the inhibition mechanism. GC-MS results showed that the addition of MSHSs could significantly reduce the emission of asphalt VOCs. Temperature influenced the emission amount of asphalt VOCs. The adsorption efficiencies of MSHSs for alkanes, hydrocarbon derivatives and polycyclic aromatic hydrocarbons are different. The inhibition mechanism indicated that the reduction of emissions of asphalt VOCs is a result of physical adsorption, rarefied concentration adsorption and chemical adsorption caused by MSHSs.